2013
DOI: 10.3171/2013.8.jns122177
|View full text |Cite
|
Sign up to set email alerts
|

The impact of radiosurgery fractionation and tumor radiobiology on the local control of brain metastases

Abstract: Object. Experience with whole-brain radiation therapy for metastatic tumors in the brain has identified a subset of tumors that exhibit decreased local control with fractionated regimens and are thus termed radioresistant. With the advent of frameless radiosurgery, fractionated radiosurgery (2-5 fractions) is being used increasingly for metastatic tumors deemed too large or too close to crucial structures to be treated in a single session. The authors retrospectively reviewed metastatic brain tumors treated at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 27 publications
1
23
3
Order By: Relevance
“…DAICc = 0 for the best-fitting model, and models with large DAICc values (>6) have much poorer support from the data. Details are discussed in the main text and in Appendix B. no support for the hypothesis that single-fraction regimens are inherently more effective than multiple fractions [14][15][16][17], and at a biologically plausible a/b ratio of 10 Gy there was some support for higher effectiveness of multiple fractions.…”
Section: Tablementioning
confidence: 83%
See 1 more Smart Citation
“…DAICc = 0 for the best-fitting model, and models with large DAICc values (>6) have much poorer support from the data. Details are discussed in the main text and in Appendix B. no support for the hypothesis that single-fraction regimens are inherently more effective than multiple fractions [14][15][16][17], and at a biologically plausible a/b ratio of 10 Gy there was some support for higher effectiveness of multiple fractions.…”
Section: Tablementioning
confidence: 83%
“…Clinical results, even for some non-standard scenarios (hyperfractionation [5], high-vs. low dose-rate brachytherapy [6], prostate hypofractionation [7]) were consistent with LQ predictions. In contrast to earlier approaches [8][9][10], there have been no major failures.Some investigators have argued that tumor eradication by large doses/fraction is dominated by distinct biological phenomena (e.g., damage to the tumor vasculature) that are qualitatively different from those operating at lower doses, and therefore are not accounted for by the LQ model [11][12][13][14][15][16][17]. By contrast, others argue [18,19] that SRT effectiveness is sufficiently explained by increased tumor doses, which destroy tumors largely through the same mechanisms that operate at lower doses.…”
mentioning
confidence: 89%
“…With regard to histology, approximately 5 % of patients enrolled on the RTOG 95-08 and EORTC prospective trials had melanoma [2,3], which is significantly lower than in the present study, and this histology has been linked to greater radioresistance [23], though not in all studies [1,4], and was not associated with more aggressive local progression in our study. A recent study found that while local control after singlefraction SRS was similar between classically radiosensitive versus radioresistant brain metastasis histologies, SRT for radioresistant histologies demonstrated worse local control than for radiosensitive histologies, with an odds ratio of 5.37 (95 % CI 3.83-6.91; p = 0.032) [24].…”
Section: Discussionmentioning
confidence: 98%
“…Fractionated SRS has become a common treatment for large tumors or lesions located near radiosensitive structures [1-6]. Although it is widely performed, an optimal uniform time interval between fractionations has not yet been established, and daily imaging is also not routinely performed during fractionated GKRS treatment [4, 5].…”
Section: Discussionmentioning
confidence: 99%
“…Fractionated stereotactic radiosurgery (SRS) is being increasingly used for large tumors or other lesions, especially those located near radiosensitive structures [1-6]. However, standard interval times between each fractionated radiosurgery have not yet been established [5].…”
Section: Introductionmentioning
confidence: 99%